Perceived entrapment predicts first-onset suicidal ideation: A longitudinal study among medical students in China - Wang, Suping; Wei, Ting; Zhu, Rui; Li, Sicong; Liu, Xinyi; Cai, Yong; Gong, Ruijie (Frontiers in Public Health, 2023)
Background The prevalence of suicidal ideation among medical students is high. Evidences indicate that entrapment is a predicting factor of suicidal ideation. This study aimed to (1) investigate the prevalence rates of first-onset suicidal ideation among Chinese medical students, (2) explore the predictive effects of alteration of entrapment on first-onset suicidal ideation. Methods This longitudinal study was conducted between 2018 and 2019, included 211 new-enrolled medical students in Shanghai. Socio-demographic (gender, major, parents’ income and academic performance), psychological (entrapment, depression, loneliness, defeat, social support and interpersonal needs) variables and suicidal ideation were collected by anonymous questionnaire. Samples were divided into 4 subgroups according to their exposure to entrapment (control, new-onset, reduced and persistent group). The primary outcome, first-onset suicidal ideation, was defined as absent suicidal ideation at baseline but present at follow-up. Results 54.98% of the participants (116/211) were female and 76.78% (162/211) majored in clinical medicine. 6.16% of the participants (16/211) reported first-onset suicidal ideation in the follow-up survey. 17.54% (37/211) reported new-onset entrapment while 12.80% (27/211) reported persistent entrapment during follow-up. Compared to control group who reported no perceived entrapment at baseline and follow-up, participants reported new-onset entrapment had the highest risk of new-onset suicidal ideation (odd ratios [OR]=14.700,95%confidence interval [CI]=2.906-74.364; adjusted OR=8.798, 95%CI=1.588-48.757; multivariate OR=8.238, 95%CI=1.394-48.693). Conclusion New-onset entrapment can significantly predict suicidal ideation. Therefore, more attention should be attached to new-onset entrapment when it comes to suicidal ideation intervention.